2000
DOI: 10.1128/mcb.20.6.2122-2128.2000
|View full text |Cite
|
Sign up to set email alerts
|

Normal Spermatogenesis in Mice Lacking the Testis-Specific Linker Histone H1t

Abstract: H1 histones bind to linker DNA and nucleosome core particles and facilitate the folding of chromatin into a more compact structure. Mammals contain seven nonallelic subtypes of H1, including testis-specific subtype H1t, which varies considerably in primary sequence from the other H1 subtypes. H1t is found only in pachytene spermatocytes and early, haploid spermatids, constituting as much as 55% of the linker histone associated with chromatin in these cell types. To investigate the role of H1t in spermatogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
124
1
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(131 citation statements)
references
References 41 publications
(51 reference statements)
4
124
1
2
Order By: Relevance
“…In addition, male germ cells contain specialized chromatin components such as H1T, a histone H1 variant specifically expressed in pachytene spermatocytes and early haploid cells (4), and HILS1, a histone H1-related protein specifically expressed in elongating and elongated spermatids (5). However, no spermatogenesis abnormalities are observed in mice lacking the H1t gene, perhaps because of redundancy with the somatic H1.1, which is also expressed at this stage (6)(7)(8)(9). This finding contrasts with the reduced fertility and defective spermiogenesis in mice lacking transition proteins 1 or 2 or haploinsufficient for protamines 1 or 2 (10-12).…”
contrasting
confidence: 52%
“…In addition, male germ cells contain specialized chromatin components such as H1T, a histone H1 variant specifically expressed in pachytene spermatocytes and early haploid cells (4), and HILS1, a histone H1-related protein specifically expressed in elongating and elongated spermatids (5). However, no spermatogenesis abnormalities are observed in mice lacking the H1t gene, perhaps because of redundancy with the somatic H1.1, which is also expressed at this stage (6)(7)(8)(9). This finding contrasts with the reduced fertility and defective spermiogenesis in mice lacking transition proteins 1 or 2 or haploinsufficient for protamines 1 or 2 (10-12).…”
contrasting
confidence: 52%
“…Each toroid contains 60 kb of DNA and is linked to other toroids by uncoiled DNA stretches. Whereas the roles of PRMs in sperm chromatin condensation and nuclear shaping are evident, the roles of H1t (16)(17)(18), TNP1 (20), and TNP2 (21) in the intermediate steps before the appearance of PRMs remain uncertain. Because HILS1 has diverged significantly from other linker histone family members and is expressed in elongating and elongated spermatids where core histones are absent, HILS1 is unlikely to function as a typical linker histone.…”
Section: Hils1 Is a Chromatin-associated Protein (Cp)mentioning
confidence: 99%
“…H1t is first detected in mid-pachytene spermatocytes, where it rapidly integrates into the chromatin, replaces most of the other somatic H1 subtypes, and persists until the elongating spermatid stage (15). Surprisingly, knockout of H1t does not affect chromatin remodeling, indicating that other known or unknown linker histones may compensate for its absence (16)(17)(18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that Brdt-mutant testes have elevated levels of H1t mRNA and that the H1t promoter is bound by BRDT, which together suggests that the H1t gene is a direct target of BRDT. While H1t is a good candidate to have a role in mediating BRDT's functions in male germ cells, it cannot be sufficient, as H1t-mutant mice have normal spermatogenesis and fertility (Drabent et al 2000;Lin et al 2000). Thus, future studies will be required to identify other BRDT target genes and to determine which of these mediates BRDT's ability to promote chromatin remodelling and germ-cell development.…”
Section: Chromatin-associated Factors That Regulate Spermatogenesismentioning
confidence: 99%